Pengaruh Kombinasi Pupuk Organik Cair dan Pupuk Anorganik serta Frekuensi Aplikasinya terhadap Pertumbuhan Tanaman Kakao (Theobroma cacao L.) Belum Menghasilkan - Ade Wachjar; Luga Kadarisman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
This research was conducted from November 2002 to Mei 2003 in Cikabayan Research Station, Faculty of Agriculture, IPB. The objective of this research was to determine the effect of combination of liquid organic fertilizer Bioton and inorganic fertilizer and frequency of application on the growth of two year old cocoa (Theobroma cacao L.). This research was arranged in randomized block design with two factors. First factor was concentration of liquid organic fertilizer Bioton with five levels, i.e. 0 ml/l + 100% inorganic fertilizer recommended dosage (i.f.r.d.), 5 ml/l + 80% i.f.r.d., 10 ml/l + 60% i.f.r.d., 15 ml/l + 40% i.f.r.d., 20 ml/l + 20% i.f.r.d.; the second factors was frequency of application of liquid organic fertilizer Bioton with two levels, i.e. once every two weeks and once every four weeks. Every treatment was replicated three times with two plants in each experimental unit. The combination of liquid organic fertilizer Bioton and inorganic fertilizer gave the best result to the diameter of stem and the primary length of branch, and the frequency of application of liquid organic fertilizer Bioton gave no effect in all parameters. Interaction between frequency of application of liquid organic fertilizer Bioton and combination of fertilizer gave the effect only to the width of the biggest leaf at the sixteen weeks after the first treatment. The spraying of liquid organic fertilizer Bioton with concentration 15 ml/l + 40% i.f.r.d., gave the best result on the growth of plant compared to other concentrations (5 ml/l + 80% i.f.r.d., 10 ml/l + 60% i.f.r.d., and 20 ml/l + 20% i.f.r.d. Frrequency of Bioton application once every four weeks was suggested. Key words : Cocoa, liquid organic fertilizer, inorganic fertilizer, concentration, rotation of application